1978
DOI: 10.1128/aac.14.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiamphenicol and Chloramphenicol in Inhibiting Neisseria gonorrhoeae Isolates

Abstract: Thiamphenicol was compared with penicillin, tetracycline, and chloramphenicol for its ability to inhibit 530 isolates of Neisseria gonorrhoeae, including 13 penicillinase-producing isolates. Thiamphenicol proved to be as active as chloramphenicol in inhibiting all of the isolates.Thiamphenicol, a chloramphenicol analog in which the nitro group has been substituted with a methylsulfonyl group (2), has been suggested as a viable alternate therapy regimen to penicillin in the treatment of infections with Neisseri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Thiamphenicol has been found to be effective in the treatment of gonococcal infections [4] and this correlated well with the in vitro activity of this drug against N. gonorrhoeae [20], In accord with the results obtained on 13 ^-lactamase-producing N. gonorrhoeae strains reported by Duck et al [21], we have observed that the activity of thiamphenicol are not affected by ^-lacta mase production. Although both chloram phenicol and thiamphenicol have primarily a bacteriostatic action, Thayer et al [20] have reported that the bacteriocidal action of thiamphenicol against N. gonorrhoeae strains is only twice that of the bacteriostat ic concentration.…”
Section: Discussionsupporting
confidence: 81%
“…Thiamphenicol has been found to be effective in the treatment of gonococcal infections [4] and this correlated well with the in vitro activity of this drug against N. gonorrhoeae [20], In accord with the results obtained on 13 ^-lactamase-producing N. gonorrhoeae strains reported by Duck et al [21], we have observed that the activity of thiamphenicol are not affected by ^-lacta mase production. Although both chloram phenicol and thiamphenicol have primarily a bacteriostatic action, Thayer et al [20] have reported that the bacteriocidal action of thiamphenicol against N. gonorrhoeae strains is only twice that of the bacteriostat ic concentration.…”
Section: Discussionsupporting
confidence: 81%
“…These effects were confirmed by growth rates close to zero at high antimicrobial concentrations ( ψ min ). Resistance to tetracycline is widespread [ 36 ] and chloramphenicol is relatively toxic and has undesirable side effects [ 37 ], so neither of these antimicrobials is currently routinely used for the treatment of gonorrhoea.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the in vitro activity of rosamicin, erythromycin, penicillin and tetracycline against N. gonorrhoeae, including P-lactamase producing isolates J. R. DILLON, P. D. DUCK, AND L. EIDUS (1978). Journal of Antimicrobial Chemotherapy, 4, [477][478][479] This paper examines the in-vitro activity of rosamicin, erythromycin, spiramycin, penicillin, and tetracycline against 517 nonpenicillinase-producing strains, and 13 penicillinase-producing strains of N. gonorrhoeae.…”
Section: -528mentioning
confidence: 99%